Devising Systen of Knowledge Management as Line in Organizational Development at Industrial Enterprise - S. P. Burlankov; M. Y. Petrenko; P. S. Burlankov; V. A. Komarov (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
Specificity of building the effective target system of knowledge management (SKM) (of the coordination type) implies its interconnection with shaping necessary competences at different level. Building organizational structure at the industrial enterprise shall be based on a set of fundamental principles, including a number of requirements to the sphere of knowledge, organizational projecting, interaction with key groups of stakeholders, etc. The major academic outcome of the article is an integral approach to formulating methodological foundations for devising the system knowledge management based on a set of key principles that should be taken into account t in organizational projecting SKM.